Comparison of the treatment efficacy of montelukast and zafirlukast in children with asthma - Volkan, Burcu; Öktem, Sedat; Boran, Perran; Tokuç, Gülnür (Haydarpaşa Numune Medical, 2020)
Introduction: Asthma is one of the most common respiratory disorders in clinical practice, affecting up to 13% of people worldwide. Leukotriene antagonists have long been used in the treatment of asthma. This study was conducted to compare the effectiveness of the montelukast and zafirlukast treatment in children diagnosed with asthma. Methods: Sixty-one patients diagnosed with asthma in the age group of 6-14 years were included in the study. Patients were consecutively divided into 2 groups, and the first group was given 5 mg of montelukast before sleep and the second group received 10 mg/day of zafirlukast in two doses. The patients were followed up monthly for 6 months. Short acting beta agonist and inhaled corticosteroid use, daytime symptoms, night awakenings, admission to the emergency department andFEV1 value were compared before and after the treatment and between two groups. Results: Significant improvement was observed in both groups during post-treatment period when compared to the pre-treatment period in terms of the short acting beta agonist and inhaled corticosteroid use, daytime symptoms, night awakenings, mean FEV I. However, no statistical difference was determined between two groups. Discussion and Conclusion: It was found that monteluksat and zafirlukast were effective in asthma treatment and there was no difference between their effects.
Keywords: Asthma; Montelukast; Zafirlukast